Niacinamide enhances cathelicidin mediated SARS-CoV-2 membrane disruption - Bhatt, Tanay; Dam, Binita; Khedkar, Sneha Uday; Lall, Sahil; Pandey, Subhashini; Kataria, Sunny; Ajnabi, Johan; Gulzar, Shah-E-Jahan; Dias, Paul M.; Waskar, Morris; Raut, Janhavi; Sundaramurthy, Varadharajan; et al. (Frontiers in Immunology, 2023)
The continual emergence of SARS-CoV-2 variants threatens to compromise the effectiveness of worldwide vaccination programs, and highlights the need for complementary strategies for a sustainable containment plan. An effective approach is to mobilize the body’s own antimicrobial peptides (AMPs), to combat SARS-CoV-2 infection and propagation. We have found that human cathelicidin (LL37), an AMP found at epithelial barriers as well as in various bodily fluids, has the capacity to neutralise multiple strains of SARS-CoV-2. Biophysical and computational studies indicate that LL37’s mechanism of action is through the disruption of the viral membrane. This antiviral activity of LL37 is enhanced by the hydrotropic action of niacinamide, which may increase the bioavailability of the AMP. Interestingly, we observed an inverse correlation between LL37 levels and disease severity of COVID-19 positive patients, suggesting enhancement of AMP response as a potential therapeutic avenue to mitigate disease severity. The combination of niacinamide and LL37 is a potent antiviral formulation that targets viral membranes of various variants and can be an effective strategy to overcome vaccine escape.